The role of si raca app in quantum learning to improve students' motivation and reading achievement - Cahyo Hasanudin; Ayu Fitrianingsih; Nofia Fitriyana; Moh. Dika Hermanto; Heny Kusuma Widyaningrum (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
Abstract: Quantum learning is very popular in educational field. It can be implemented easily in elementary school. It will be more interesting when it is collaborated with an application as a learning media. This study aims to investigate the design of quantum learning which is collaborated with Si Raca app and to investigate students’ motivation and reading achievements in it. This study is classroom action research that involves 24 students in the first grade of SD Islam Darussalam Kedungrejo, Sumberrejo, Bojonegoro Regency, East Java. This study utilizes research instruments in form of observation sheets which implement the aspect of ARCH and reading tests with indicators of fluency, accuracy, pronunciation, and intonation. Research procedures are started from analyzing problems, designing actions, implementing actions, and reflecting. The data is analyzed using likert scale and it is calculated using simple formula. Moreover, it is consulted with interval scores. Results of study show that the quantum learning collaborated with Si Raca app in early reading is designed using innovative and interactive approach which implements the syntax of TANDUR. There are 50% of students who improve their motivation and reading achievements very well. It can be concluded that Si Raca app has important role in quantum learning. This application is a learning media which is useful for students in improving their motivation and reading achievements.